2004
DOI: 10.1515/ijamh.2004.16.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Transition to adult care for adolescents with sickle cell disease: Results of a national survey

Abstract: The objective was to present the 'voice' of adolescents with sickle cell disease (SCD) as part of the discussion of transition issues by identifying and documenting their expressed concerns and expectations, as well as what program priorities they perceive would facilitate a smooth transition to adult care. Cross-sectional data were collected by means of structured questionnaire interviews, using standard instruments. A volunteer sample of 172 adolescents with SCD aged 14 years and older still in pediatric car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 23 publications
3
68
1
Order By: Relevance
“…Telfair et al (46) assessed provider perceptions regarding transition services, and although most agreed that transition programs were necessary, few did anything to facilitate the transition process. Those who care for both adolescents and adults expected to see the patient with their parent, whereas those who cared only for adults expected to see the adolescent alone.…”
Section: Transitioning Between Pediatric and Adult Carementioning
confidence: 99%
“…Telfair et al (46) assessed provider perceptions regarding transition services, and although most agreed that transition programs were necessary, few did anything to facilitate the transition process. Those who care for both adolescents and adults expected to see the patient with their parent, whereas those who cared only for adults expected to see the adolescent alone.…”
Section: Transitioning Between Pediatric and Adult Carementioning
confidence: 99%
“…This transfer of care from pediatric services to adult services in patients with chronic illness is associated with increased morbidity and mortality for these patients (Brousseau, Owens, Mosso, Panepinto, & Steiner, 2010;Cadario et al, 2009;Debaun & Telfair, 2012). This has been attributed to a multitude of factors including patients' lack of knowledge regarding the transition process, fears that adult providers will not understand their needs, changes in insurance providers, and (Quinn, Rogers, McCavit, & Buchanan, 2010) inability to get appointments due to insurance status (Telfair, Ehiri, Loosier, & Baskin, 2004).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
“…The primary concern of young adults regarded their ability to pay and acceptance by adult care providers [18]. Studies have identified a lack of information on transition, fear of departing from their familiar healthcare provider [13] and embarking on a relationship with a new provider [17] as major concerns on transition to adult care. Once young patients were moved to adult care successfully, they acknowledged benefits of the adultoriented system even though most young patients were concerned about adaptation prior to transition [17].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have assessed the challenges faced when youth with special health care needs seek transition to adult-oriented care [8][9][10][11][12][13]. A recent survey was conducted among 45 large (≥100 pediatric patients) sickle cell centers in the US that care for pediatric patients to describe current transition practices and identify areas for improvement [14].…”
Section: Introductionmentioning
confidence: 99%